Comparison of Strength Parameters in Amputee Football Players According to the Degree of Amputation - Ahmet Kurtoğlu, Nurettin Konar, Faruk Akçinar, Bekir Çar, Yağmur Akkoyunlu (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Amputee football is a sports branch for the disabled that has become popular in recent years. However, studies on determining and improving the performance parameters of amputee football players are limited. Aim: The purpose of this study is to compare the strength parameters of amputee football players (AF) depending on the degree of amputation. Methods: 35 amputee football players aged 16-48 years, actively participating in amputee football superleague, participated in our study. Descriptive research, one of the quantitative data collection instruments, was chosen as the research type. In the study, participants with transtibial amputation (TTA) (n=17, age=32.41±2.13, height= 173.47±1.82, weight=69.17±2.47) and transfemoral amputation (TFA) (n=18, age=26.50±1.26, height= 177.00±1.29, weight= 72.22±2.92) were divided into two groups according to amputation level. After recording the demographic data (age, height, weight, amputation level) of the participants, the waist-to-hip ratio was measured. During the study, participants’ back, leg, and handgrip strengths were measured using a Takai brand dynamometer. For the statistical operations in the study, SPSS 25 package programme was used. Independent Samples T Test was used for the analysis of variables between groups. The Pearson correlation test was used to determine the relationship between the variables. Results: According to the results of the study, no significant difference was found between the TTA and TFA groups in terms of back strength, leg strength, hand grip strength, and hip-to-hip ratio (p > 0.05). Pearson’s correlation analysis between variables revealed that for participants with TTA, there was a relationship between back strength and height (p=.031) and weight (p=.012), between leg strength and waist circumference (p=.037) and hip circumference (p=.035), and between handgrip strength and height. (p=.006), a high correlation was found between waist-to-hip ratio and age (p=.002), weight (p=.004) and BMI (p=.000) (p < 0.05). A high correlation was found between back strength, leg strength (p=.007) and handgrip strength (p=.020), waist-hip ratio and BMI (p=.032) in participants with TFA (p<0.05). Conclusion: In evaluating the research results, it was found that the level of amputation had no effect on back, leg, and hand grip strength. In addition, it was found that there was a significant relationship between the participants’ leg strength-back strength, back strength-hand grip strength, back strength-height, and hand grip strength-height. It is anticipated that in more comprehensive studies in which 1st and 2nd division amputee football teams may participate, different results will be obtained.